Actualities in the phytochemical research on selected terpenes - Jerković Igor; Maleš Željan; Friščić Maja (Acta Pharmaceutica, 2019)
A short review of our recent research on the essential oil phytochemical composition of Petasites albus (L.) Gaertn. and Petasites hybridus (L.) G. Gaertn., B. Mey. & Scherb. (Asteraceae) as well as on the oils of Globularia cordifolia L., Globularia meridionalis (Podp.) O. Schwarz and Globularia punctata Lapeyr. (Plantaginaceae) is presented. All essential oils contained a variety of oxygenated sesquiterpenes among their major constituents, including a bakkane type sesquiterpene fukinanolid (bakkenolide A). The paper is focused on: i) a short overview of the abundance of major terpenes in the essential oils of Petasites and Globularia species from Croatia; ii) possible biosynthetic pathways of major identified sesquiterpenes; and iii) biological activities (literature data) of major sesquiterpenes from Petasites and Globularia species.